Trustees in insolvency: the manifestation of Australia's fascination with the use of the trust as a business vehicle. Issue 10 (5th December 2019) - Morrison, David
Abstract: Corporate trustees are prevalent in the operation of businesses in Australia. However, the Corporations Act in Australia makes no express provision for the insolvency of a corporate trustee. Given that the trading trust is often used for commercial purposes in Australia, together with a corporate trustee, it is important that the law reflects a clear and consistent approach in the event of the insolvency of a business owned by a trading trust. It is opined that the position of an insolvent corporate trustee ought to be, as far as possible, dealt with consistently with that of a business held directly by a company. Notwithstanding the recommendations of a 1988 inquiry reporting looming difficulty, no legislative correction has occurred. Consequently, a series of conflicting case law follows. This article considers recent developments in respect of judicial consideration in the context of the recommendations made more than 30 years previously.